Evaluation of the School Literacy Movement Program with the CIPP Model on Reading Literacy in Primary Schools in Gunung Kidul, Yogyakarta - Utami, Wulan Tri Puji; Nurhayati, Riana; Anwar, Muhammad Saiful; Hajaroh, Mami; Rohman, Arif; Sudarno, Sudarno; Fajri, Hanif Musthofa Al; Lina Rahmawati; Nurkhayati, Lily Siti; Azhar, Muhammad Akmal (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2025)
This study uses a quantitative approach with a descriptive evaluative type to assess the effectiveness of the School Literacy Movement Program (GLS) in elementary schools in Gunung Kidul Regency, Yogyakarta. In this Context, reading literacy challenges are still evident in the uneven interest in reading, limited and diverse reading materials, variations in the readiness of school facilities/infrastructure, and parental involvement and consistency in implementing literacy activities. The study evaluated GLS using the CIPP (Context, Input, Process, Product) model based on the perceptions of program implementers (principals and teachers). Data were collected through questionnaires from 9 principals and 54 teachers in 9 elementary schools and analyzed using IBM SPSS Statistics 29 (mean and standard deviation). The results show Context = 3.55 (very good), Input = 3.35 (very good), Process = 3.10 (good), and Product = 3.50 (perfect). These findings confirm that GLS has a strong policy foundation and adequate resource support, followed by generally exemplary implementation, and contribute to improving students' reading literacy. The implementation of GLS at Gunung Kidul Elementary School is effective. However, it needs to be strengthened in terms of process, especially consistency of implementation, active student participation, diversification of reading materials, support from parents/community, and ensuring the sustainability of resources so that the program's impact is more equitable and sustainable.